Grenvillian basement in the northern Cape Breton Highlands, Nova Scotia - Barr, Sandra M.; Raeside, Robert P.; van Breemen, Otto (Canadian Journal of Earth Sciences, 1987)
The northernmost Cape Breton Highlands are underlain by the Blair River Complex, a distinctive assemblage of basement rocks including felsic and mafic gneisses, foliated gabbroic to granitic rocks, anorthosite, and foliated and unfoliated varieties of syenite. Major faults and mylonite zones separate the complex from schists, gneisses, and granitoid rocks typical of the rest of the Cape Breton Highlands. U–Pb dating of zircon from the Lowland Brook syenite of the Blair River Complex indicates a metamorphic age of [Formula: see text] and an igneous age of 1100–1500 Ma. These ages and the distinctive rock assemblage allow the Blair River Complex to be correlated with the Grenvillian rocks in the Long Range Inlier and Indian Head Range Complex of western Newfoundland. This is the first confirmed report of Grenvillian basement in Cape Breton Island, and it places new constraints on correlations between Newfoundland and the northern mainland Appalachians.